1,2-Dihydroxyxanthone: Effect on A375-C5 Melanoma Cell Growth Associated with Interference with THP-1 Human Macrophage Activity - Viviana Silva; Fátima Cerqueira; Nair Nazareth; Rui Medeiros; Amélia Sarmento; Emília Sousa; Madalena Pinto (MDPI AG, 2019)
Xanthones have been suggested as prospective candidates for cancer treatment. 1,2- dihydroxyxanthone (1,2-DHX) is known to interfere with the growth of several cancer cell lines. We investigated the effects of 1,2-DHX on the growth of the A375-C5 melanoma cell line and THP-1 human macrophage activity. 1,2-DHX showed a moderate growth inhibition of A375-C5 melanoma cells (concentration that causes a 50% inhibition of cell growth (GI50) = 55.0 ± 2.3 µM), but strongly interfered with THP-1 human macrophage activity. Supernatants from lipopolysaccharide (LPS)-stimulated THP-1 macrophage cultures exposed to 1,2-DHX significantly increased growth inhibition of A375-C5 cells, when compared to supernatants from untreated LPS-stimulated macrophages or to direct treatment with 1,2-DHX only. 1,2-DHX decreased THP-1 secretion of interleukin-1β (IL-1β) and interleukin-10 (IL-10), but stimulated tumor necrosis factor-α (TNF-α) and transforming growth factor-β1 (TGF-β1) production. This xanthone also inhibited nitric oxide (NO) production by RAW 264.7 murine macrophages, possibly through inhibition of inducible NO synthase production. In conclusion, these findings suggest a potential impact of 1,2-DHX in melanoma treatment, not only due to a direct effect on cancer cells but also by modulation of macrophage activity.